Home - A World of Serious Life: An Overview of Rituality and Materiality in our Homes - Bara´nski, Janusz (Ethnologia Fennica, 2012)
ln his well-known writings on the anthropology of daily life, Roch Sulima (2000) reflects on the topic of life on an allotment. The use of the term 'life' in relation to allotments is perhaps a bit exaggerated. After all, the time a person spends on his or her allotment is usually a few hours at the weekend, weeding fruit and vegetable beds and patches or digging up a few carrots. However, some allotment holders may sometimes spend all of their time away from work, e.g. during the summer holidays, on their allotments, living their allotment lives in full. These obvious statements appear to have little importance when contrasted with the concept formulated by the author, not only because of the similarities between the architecture of allotments and that of fairy tales, but also because he uses the concept of ritual, which, according to the author, represents the very source of all the things an allotment holder does on his or her allotment.